Physics and chemistry of graphene graphene to nanographene - Enoki, Toshiaki; Ando, Tsuneya 1945- (Jenny Stanford Publishing, 2020)
This book comprehensively discusses the fundamental issues related to the electronic, magnetic, and chemical properties of condensed polycyclic hyodrocarbon molecules, nanographene, and graphene.